Developing game-based learning and English learning achievement of grade 1 students - Sirisarn, Tawanna; Prasertsang, Parichart (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
The first objective aims to develop English learning activities using game-based learning for enhancing the vocabulary retention of grade 1 students, to be effective according to the 70/70 criterion. The second objective aims to compare the learning achievement before and after. The participants of this research consisted of 32 grade 1 students in Semester 2, Academic Year 2023. The research tools were divided into two categories, including 3 learning management plans, a vocabulary memorization ability test in flashcard format with 20 items, and a learning achievement test, which was 20 items of multiple choices. The statistics used in data analysis were percentage, mean, standard deviation, and dependent t-test. The results of the research found that the game-based learning plan for grade 1 students had an efficiency of 86.41/79.38, which is higher than the set criteria of 70/70. They had higher academic achievement after learning management than before learning at a statistical significance of .05. English learning and other fields of study can benefit from the implementation and more research in various group of the study.